Multiscale vortical phonons and vorticity wave vortices as coherent excitations in two-dimensional dusty plasma crystals - Wei-Shuo Lo; Chen-Yu Siao; Yi-Cheng Zhao; Lin I (Physical Review Research, 2025)
Counterintuitively, cooperative spatiotemporal motions and localized coherent entities (CEs) with distinct topological features can emerge in various extended systems exhibiting disordered multiscale fluctuations. Examples include multiscale vortices in nonlinear hydrodynamic turbulent flows and multiscale wave vortices in traveling acoustic wave turbulence. However, their fundamental nature and generic behaviors in stochastically driven, disordered multiscale linear waves remain elusive. Here, we utilize two-dimensional crystals supporting thermally excited, multiscale disordered vibrations, as a model system to address these issues. By combining two-dimensional dusty plasma crystal experiments with numerical simulations of Yukawa and Lennard-Jones crystals, we report the following observations at the discrete level: (a) multiscale vortical phonons (also named as vorticity waves, VWs), in the form of propagating vortices with alternating signs of vorticities and varying vortex shape, predominately contributed by the superposition of transverse waves, as basic cooperative acoustic vibrations; and (b) vorticity wave vortices (VWVs), where the VW crest surfaces helically wind around screw-dislocation filaments in the xyt space, as localized CEs in VWs. These VWVs exhibit stretched-exponential lifetime distribution and short-range spatial correlations.